2013
DOI: 10.2478/s11687-013-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of monepantel against lower developmental stages of a multi-resistant and susceptible Haemonchus contortus isolates: an in vitro study

Abstract: SummaryMonepantel (MOP) belongs to a new class of anthelmintic compounds, the amino-acetonitrile derivates, which have a different mode of action as the currently used anthelmintics. Many present studies confirmed the high efficacy of MOP against fourth larval and adult stages of Haemonchus contortus. The objective of this study was to determine in vitro efficacy of MOP against lower development stages (eggs, L 1 -L 3 larvae) and to compare it between resistant and susceptible isolates of H. contortus. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Because of this, it is necessary to highlight the importance of using standard substances in order to establish cutoff criteria and reduce the variability of the criteria to a minimum. Although in the present study the approach used to determine the cutoff values (LC 50 ) for MPT was through the commercial anthelmintic (Zolvix ® ), it was justified by the fact that in previous studies Zolvix ® presented better performance than MPT (chemical base), for detecting resistance to LDT among H. contortus (Lecová et al, 2013;Raza et al, 2016;Kotze et al, 2018;Gainza et al, 2019).…”
Section: /10mentioning
confidence: 98%
“…Because of this, it is necessary to highlight the importance of using standard substances in order to establish cutoff criteria and reduce the variability of the criteria to a minimum. Although in the present study the approach used to determine the cutoff values (LC 50 ) for MPT was through the commercial anthelmintic (Zolvix ® ), it was justified by the fact that in previous studies Zolvix ® presented better performance than MPT (chemical base), for detecting resistance to LDT among H. contortus (Lecová et al, 2013;Raza et al, 2016;Kotze et al, 2018;Gainza et al, 2019).…”
Section: /10mentioning
confidence: 98%
“…The efficacy of MOP against lower developmental stages (eggs and L 1 –L 3 larvae) of H. contortus isolates was studied by Lecová et al (2013). In this study, two in vitro methods were used.…”
Section: Mop Efficacy Studiesmentioning
confidence: 99%
“…Both larval tests rely on the development of eggs to L 3 larvae (Coles et al 2006). The study of Lecová et al (2013) showed that MOP had no significant ovicidal effect, which means that the MOP do not affect the eggs and therefore they have the potential to develop to infective larvae. On the other hand, MOP exhibited significant larvicidal effect, what conversely means that the parasites will not be able to develop to infective larvae.…”
Section: Ruminant Parasitesmentioning
confidence: 99%
“…This results in a constant uncontrolled flux of ions and finally in a depolarization of muscle cells. [13] The present information about MOP has been reviewed recently. [12] MOP is also effective against nematodes' earlier larval stages (L 1 -L 3 ) and larval susceptibility is not dependent on the drug-sensitivity status of the nematode isolate.…”
Section: Introductionmentioning
confidence: 99%
“…[12] MOP is also effective against nematodes' earlier larval stages (L 1 -L 3 ) and larval susceptibility is not dependent on the drug-sensitivity status of the nematode isolate. [13] The present information about MOP has been reviewed recently. [14] Since 2010, MOP has been used in the therapy of nematode infections in sheep mostly with success.…”
Section: Introductionmentioning
confidence: 99%